2019
DOI: 10.1002/tie.22105
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of expatriates adjustment in distant subsidiaries: A field study of a sub‐Saharan African institutional distance

Abstract: The aim of this study is to investigate the determinants of expatriates' adjustments in distant and complex multinational subsidiaries. Using the institutional theory as basis for expatriates' assignments in complex subsidiaries, the work employed a sequential mixed methodology of data collection. An in-depth face-to-face interview with 21 senior expatriate executives and a quantitative survey of 204 expatriates working in various multinational subsidiaries in Ghana served as data for the work. Consequently, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…A different but related study by Zhang and Peltokorpi (2016) found that expatriate host country language proficiency has multifaceted effects on expatriates' work and nonwork adjustment. In other related studies, Abugre, Williams, and Debrah (2019); Abugre, Yaw, and Debrah (2019) found that cross‐cultural communication significantly determines expatriate adjustment. Overall, based on the review of the related literature summarized above, it is likely that the ability of Chinese expatriates to speak and communicate effectively in English will positively affect their adjustment to Nigeria.…”
Section: Cross‐cultural Trainingmentioning
confidence: 89%
See 1 more Smart Citation
“…A different but related study by Zhang and Peltokorpi (2016) found that expatriate host country language proficiency has multifaceted effects on expatriates' work and nonwork adjustment. In other related studies, Abugre, Williams, and Debrah (2019); Abugre, Yaw, and Debrah (2019) found that cross‐cultural communication significantly determines expatriate adjustment. Overall, based on the review of the related literature summarized above, it is likely that the ability of Chinese expatriates to speak and communicate effectively in English will positively affect their adjustment to Nigeria.…”
Section: Cross‐cultural Trainingmentioning
confidence: 89%
“…Much research has been conducted on CCT and expatriate adjustment (Caligiuri et al, 2001; Lai & Yang, 2017; Mendenhall et al, 2004; Morris & Robie, 2001; Selmer, 2005; Wang et al, 2017; Waxin & Panaccio, 2005; Wurtz, 2014). Our review of the literature on CCT and expatriate adjustment shows that there is a lack of research on this topic when it comes to Africa and Nigeria, with the notable exceptions of some exploratory studies (Abugre, Williams, & Debrah, 2019; Abugre, Yaw, & Debrah, 2019; Okpara, 2016; Okpara & Kabongo, 2011, 2017). To the best of our knowledge, this is the first empirical research study investigating the influence of predeparture and postarrival CCT on the adjustment of Chinese expatriates in Nigeria.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, other scholars have investigated how expatriates from different cultures transition and adapt to the African culture (e.g. Abugre and Debrah, 2019;Abugre et al, 2020;Okpara and Kabongo, 2011) yet little is known about the support they receive from the organisation which is crucial for their adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the cultural differences that affect people's attitudes and behaviors is essential for better intercultural cohesion. Findings from Abugre et al, (2020) study reveal that host country culture plays a significant role in determining expatriate adjustment in distant subsidiaries. There are many examples of how cultural differences affect behavior patterns.…”
Section: Cultural Intelligence and Cross-cultural Adjustment: Hypothesis Developmentmentioning
confidence: 96%